Formulation of marigold (Tagetes erecta L.) flower extract in peel off mask using polyvinyl alcohol and polyethylene glycol 6000 base - Dian Ermawati; Vini Nurbaiti; Uswatun Chasanah (Pharmaciana, 2019)
Flavonoid and Carotenoids in marigold extract can act as a potent antioxidant. The using of antioxidant peel off face mask is very practical  The aim of this research is to determine the effect of Marigold (Tagetes erecta L.) extract concentration in Polyvinyl alcohol (PVA) and Polyethylene Glycol (PEG) 6000 peel off mask base to the physical characteristic and stability. Marigold flower ethanol extract in 3 different concentration (F1 3 %, F2 4% and F3 6%) were formulated in peel off mask using PVA and PEG 6000 base. Evaluation of peel off mask including physical characteristics (organoleptic, homogeneity, viscosity, spreadability, and drying time), chemical (pH) and  stability.The  results showed  that all of the formulas have a brown color and soft textured gel. All of the formulas were homogeneous. In viscosity, a test showed that F1, F2, F3 (18.466; 22.533; 28.133cps), drying time test (29.1; 26.29; 24.64 minutes), and pH (5.5I; 4.71; 4.59). There was no significant difference in viscosity, pH, drying time and spreadability test. The result of a stability test and freeze-thaw showed that all of the formulas were stable and there were no significant changes in organoleptic and pH. Marigold extract until 6 % can be formulated in peel off mask using PVA and PEG 6000 base. All of the formulas showed good stability and good physical characteristic.